Torts: a guide for the perplexed - Fridman, G. H. L. (LexisNexis Canada Inc., 2017)
"The aim of this text is to provide a revealing background to the law of torts for its better understanding and appreciation by those who find themselves somewhat confused as to the true nature and scope of this part of the law and would like some clarification. This book consists of a number of independent essays that raise and discuss ideas which permeate the modern content and function of the law of torts. They also provide an historical context that allows the reader to better understand tort law concepts. Their purpose is to stimulate the interest of the read and encourage them to dive further into this area of the law. As such, this text is broader in scope than a standard primer of the law of torts express in simple language."-- Provided by publisher.